Cytokine expression in chronic inflammatory disease. - Brennan, F; Maini, R; Feldmann, M (1995)
In chronic inflammatory diseases, typified by rheumatoid arthritis, we speculated that upregulation and/or disregulation of cytokine production in inflamed tissue might contribute both directly and/or indirectly to the pathology in the synovial joint tissue. This chapter summarises studies performed principally by our own group over the last 9 years or so, but also by others in the field who have investigated the expression of cytokines in RA. From our studies we identified one particular cytokine, tumour necrosis factor alpha (TNF alpha) as an important, 'pivotal', molecule in the disease process. This concept has led to the initiation and completion of the first successful clinical trials in RA patients to verify this hypothesis, using a neutralising antibody to TNF alpha.